Social and occupational reintegration of persons aged 45+ in social cooperatives - Sobczak, Michał Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Social cooperatives are one of the tools that prevent social exclusion by delivering a special welfare service – social employment. The risk of social exclusion caused by prolonged unemployment is particularly high among people aged 45+. The paper tests the extent to which social cooperatives implement a welfare service in the form of social employment and the related social and occupational reintegration, particularly with respect to people aged 45+. The paper presents the results of a survey of social cooperatives’ members in the Łódź region, during which various aspects of their work in these organizations were investigated. An analysis was conducted to assess social cooperatives’ potential for enabling social and professional reintegration of people threatened by social exclusion, particularly those in the age group 45+.